2021
DOI: 10.1371/journal.pone.0261353
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the gut microbiome and osteoarthritis: A systematic review of literature

Abstract: Background Along with mechanical and genetic factors, emerging evidence suggests that the presence of low-grade inflammation has a role in the pathogenesis of osteoarthritis (OA) and seems to be related to the microbiome composition of the gut. Purpose To provide evidence whether there is clinical or preclinical evidence of gut-joint axis in the pathogenesis and symptoms of OA. Methods An extensive review of the current literature was performed using three different databases. Human, as well as animal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 73 publications
0
18
0
1
Order By: Relevance
“…In our view, B deficiency from the symbiosis process may lead to dysbiosis and gut permeability by decreasing the concentration of AI-2B. At the same time, decreasing the concentration of B in the colonic mucus induces the formation of bacterial metabolites and proinflammatory cytokines, which could help the pathophysiological mechanisms of osteoarthritis (OA) [ 112 , 113 , 114 ]. This mechanism could explain why in areas with a high content of B, people have a low OA index [ 115 ].…”
Section: Are Nob Species Essential For Healthy Human/animal Microbiom...mentioning
confidence: 99%
“…In our view, B deficiency from the symbiosis process may lead to dysbiosis and gut permeability by decreasing the concentration of AI-2B. At the same time, decreasing the concentration of B in the colonic mucus induces the formation of bacterial metabolites and proinflammatory cytokines, which could help the pathophysiological mechanisms of osteoarthritis (OA) [ 112 , 113 , 114 ]. This mechanism could explain why in areas with a high content of B, people have a low OA index [ 115 ].…”
Section: Are Nob Species Essential For Healthy Human/animal Microbiom...mentioning
confidence: 99%
“…The mechanism of the association of endometriosis with a wide range of other symptoms, such as depression, lower BMI, autoimmune diseases, allergies, etc., are not clear. However, considering the recently observed associations between the intestinal microbiome and a whole range of effects on the brain, immunology, and rheumatoid arthritis it is attractive to speculate that many of these associations with endometriosis might also find their origin in hereditary factors increasing the risk of endometriosis and changing the bowel microbiota as reviewed in 42 articles in 2021 only [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]). The association with sexual dysfunction seems to be caused by the pain, which is a strong inhibitor of sexuality [ 61 , 62 , 63 , 64 ].…”
Section: Clinical Consequences Of Our New Understandingmentioning
confidence: 99%
“…Though various reviews could be found on GM and OA [ 163 , 164 ], only one considered the impact of GM composition on pain symptoms [ 165 ]. Sánchez Romero et al, who reviewed GM and OA pain, found only three studies on the subject.…”
Section: Gm and Musculoskeletal Painmentioning
confidence: 99%